The Versatility of Sirtuin-1 in Endocrinology and Immunology - Rasha, Fahmida; Mims, Brianyell McDaniel; Castro-Piedras, Isabel; Barnes, Betsy J.; Grisham, Matthew B.; Rahman, Rakhshanda Layeequr; Pruitt, Kevin (Frontiers in Cell and Developmental Biology, 2020)
Sirtuins belong to the class III family of NAD-dependent histone deacetylases (HDAC) and are involved in diverse physiological processes that range from regulation of metabolism and endocrine function to coordination of immunity and cellular responses to stress. Sirtuin-1 (SIRT1) is the most well-studied family member and has been shown to be critically involved in epigenetics, immunology, and endocrinology. The versatile roles of SIRT1 include regulation of energy sensing metabolic homeostasis, deacetylation of histone and non-histone proteins in numerous tissues, neuro-endocrine regulation via stimulation of hypothalamus-pituitary axes, synthesis and maintenance of reproductive hormones via steroidogenesis, maintenance of innate and adaptive immune system via regulation of T- and B-cell maturation, chronic inflammation and autoimmune diseases. Moreover, SIRT1 is an appealing target in various disease contexts due to the promise of pharmacological and/or natural modulators of SIRT1 activity within the context of endocrine and immune-related disease models. In this review we aim to provide a broad overview on the role of SIRT1 particularly within the context of endocrinology and immunology.